Gerakan Perlawanan Terhadap Sengketa Tanah Adat Melalui Politik Tubuh Perempuan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The government program for the existence of the Pandumaan and Sipituhuta customary law communities which are customary land communities is regulated in Article 5 Number. 5 of 1960 concerning Agrarian Principles, there is a statement that the existence of customary law communities is recognized if they still exist and are active. As society develops and grows, the need for land for land makes the government sometimes take customary land rights from customary communities, thus creating conflict between customary communities and the government. The conflict between the Pandumaan and Sipituhuta customary law communities and the government also involves the role of women as part of the body politics that plays a role in defending the rights of customary law communities. The role of women here is not much different from the role of men so that gender disparities are not visible. The conflict between the Pandumaan and Sipituhuta customary law communities and the government is still very vulnerable to misuse of regulations or legislation that regulate it regarding Customary Law Communities as the basis for legal science which will be deepened through Foucault's theory of power.